1999
DOI: 10.1063/1.124891
|View full text |Cite|
|
Sign up to set email alerts
|

High-Tc second-order gradiometer for magnetocardiography in an unshielded environment

Abstract: We have fabricated planar first-derivative gradiometers in which an asymmetric flux transformer patterned in a single-layer YBa2Cu3O7−x film is permanently bonded to a directly coupled magnetometer based on a dc superconducting quantum interference device (SQUID). The gradiometer base line is 48 mm. The common mode rejection of uniform magnetic fields is typically one part in a few hundred. The outputs of two such gradiometers are subtracted digitally to form a second-derivative gradiometer. Additionally, thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…1,[3][4][5][6][7][8][9][10][11][12] The first-order axial gradiometer recording results are in less distortion than the second-order axial gradiometer with the same baseline for HT c SQUID MMCG system in a MSR. 1,6,12 The drawback of such gradiometers is impossible to keep in parallel with each other strictly. Considering the flexibility and stability of gradiometer, software gradiometer is an available way to obtain the high quality MCG signals that has been demonstrated by some impressive researches using various digital signal processing methods.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,[3][4][5][6][7][8][9][10][11][12] The first-order axial gradiometer recording results are in less distortion than the second-order axial gradiometer with the same baseline for HT c SQUID MMCG system in a MSR. 1,6,12 The drawback of such gradiometers is impossible to keep in parallel with each other strictly. Considering the flexibility and stability of gradiometer, software gradiometer is an available way to obtain the high quality MCG signals that has been demonstrated by some impressive researches using various digital signal processing methods.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that MCG provides practical and informative for diagnosing of the pre-excitation syndromes, ischemic heart disease (IHD) and the accurate localization of arrhythmogenic substrates and accessory pathways for catheter ablation or surgery with sufficient spatial accuracy necessary for clinical purpose, [1][2][3] this useful technique based on superconducting quantum interference device (SQUID) magnetometer, no matter on cryogenic or hyperthermia, have been developed. [4][5][6] Conceptually, MCG is not new. Actually, the first MCG recording system was carried out only after the invention of the SQUID in early 1970s.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until present, first-and second-order HTS SQUID gradiometers, measuring axial or tangential fields, were demonstrated and MCG data recorded without magnetic shielding. [3][4][5] In these measurements, low-pass filters with a cutoff frequency of below 30 Hz were used to reduce the power line interference at 50 Hz, or a 60 Hz notch filter was used. 5 However, the frequency components of the MCG higher than 50 and 60 Hz contain significant information.…”
mentioning
confidence: 99%
“…[3][4][5] In these measurements, low-pass filters with a cutoff frequency of below 30 Hz were used to reduce the power line interference at 50 Hz, or a 60 Hz notch filter was used. 5 However, the frequency components of the MCG higher than 50 and 60 Hz contain significant information. 2,6 For clinical diagnostics, a MCG system has to have a bandwidth wider than 100 Hz, so that further development is warranted.…”
mentioning
confidence: 99%